Notes to Philosophy 167: Class 10 -- Huygens and the Beginnings of Rational Mechanics -- Part 1 - Part 3. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Synopsis: The Development of Astronomy: 1642-1672 -- Post-Galilean Developments in Mechanics -- Christiaan Huygens (1629-1695): a chronology until 1673 -- Huygens and the Measurement of g (1659); Generally corresponds to the video segment: Class 10, Part 1 - 3.